2022
DOI: 10.1111/1750-3841.16254
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the formation mechanism and detection technology of bread flavor

Abstract: With a long history of fermentation technology and rich flavors, bread is widely consumed by people all around the world. The consumer market is huge and the demand is wide. However, the formation mechanism of bread baking flavor has not been completely defined. In order to improve the breadmaking process and the quality of bread, the main flavor substances produced in bread baking, the formation mechanism, and the detection technology of bread baking flavor are carefully summarized in this paper. The generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…As previously reported, sourdough fermented by consortia of LAB and yeast confers a unique and more complex flavor to wheat bread ( Suo et al, 2021 ; Y. Yang et al, 2022 ). This is likely due to the synergic metabolisms of S. cerevisiae and L. plantarum that can cause the release of special aroma-active compounds of bread, in the meantime the decreased amount and consumption of unpleasant indole ( Zhang et al, 2023a ).…”
Section: Discussionmentioning
confidence: 67%
“…As previously reported, sourdough fermented by consortia of LAB and yeast confers a unique and more complex flavor to wheat bread ( Suo et al, 2021 ; Y. Yang et al, 2022 ). This is likely due to the synergic metabolisms of S. cerevisiae and L. plantarum that can cause the release of special aroma-active compounds of bread, in the meantime the decreased amount and consumption of unpleasant indole ( Zhang et al, 2023a ).…”
Section: Discussionmentioning
confidence: 67%
“…The differentiation along PC1 (representing ~45% of variance) was mainly between crumbs/crusts, which directly corresponds to higher proportions of Maillard and caramelization products in crusts ( Figure 6 , Supplementary Table S3 ). A closer inspection of individual compounds across samples showed two main clusters of compounds over-accumulated in crusts, including alkylpyrazines, furans, pyrroles, maltol, and “Strecker aldehydes” ( 33 ), formed during later stages of the Maillard reaction ( Supplementary Figure S4 ). Milling type was the secondary driving factor in determining bread aroma, as evidenced by a segregation across PC2 (representing ~31% of variance, Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that only a handful of compounds retained their significantly elevated levels in landrace breads as well as in the flours used for baking ( Supplementary Figure S4 , Supplementary Tables S2 , S3 ). The entire dataset of detected metabolites ( n = 205) was cross-referenced to the current literature detailing odor active compounds in bread ( 10 , 33 ). We found that our dataset contained 41 such compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The flavor of edible fungi is mainly composed of volatile and nonvolatile components. Volatile aroma components are mainly brought by the sense of smell such as 1‐octen‐3‐ol and 1‐octen‐3‐one (Li et al., 2015), whereas the taste active substances are mainly nonvolatile components like soluble carbohydrate and flavor amino acids (Yang & Gu, 2013), which are more inclined to taste and texture brought by the sense of taste, whereas nonvolatile components have received more attention in the flavor research and food applications (Li et al., 2020).…”
Section: Introductionmentioning
confidence: 99%